HPLC-DAD based method for the quantification of flavonoids in the hydroethanolic extract of Tonina fluviatilis Aubl. (Eriocaulaceae) and their radical scavenging activity - Amorim, Marcelo R. De [UNESP]; Rinaldo, Daniel [UNESP]; Amaral, Fabiano P. Do [UNESP]; Vilegas, Wagner [UNESP]; Magenta, Mara A. G.; Vieira Jr, Gerardo M.; Santos, Lourdes Campaner dos [UNESP] (Sociedade Brasileira de Química, 2014)
This article describes the isolation and identification of flavonoids in the hydroethanolic extract of the aerial parts from Tonina fluviatilis and evaluation of their antiradical activity. A method based on HPLC-DAD was developed and validated for detecting and quantifying flavonoids in hydroethanolic extracts. The flavonoids identified and quantified in the extract were 6,7-dimethoxyquercetin-3-O-β-D-glucopyranoside (1), 6-hydroxy-7-methoxyquercetin-3-O-β-D-glucopyranoside (2), and 6-methoxyquercetin-3-O-β-D-glucopyranoside (3). The developed method presented good validation parameters, showing that the results obtained are consistent and can be used in ensuring the quantification of these constituents in the extracts. Compounds 2 and 3 showed strong antiradical activity when compared with the positive controls (quercetin and gallic acid).
Keywords: Eriocaulaceae; Tonina fluviatilis; flavonoids; HPLC-DAD; antiradical activity